2019
DOI: 10.22495/cocv16i4art7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between tax avoidance, company characteristics and corporate governance: Evidence from Greece

Abstract: The purpose of this paper is to research a possible relationship between corporate tax avoidance with corporate governance characteristics such as board independence, the type of auditing company and the concentration of ownership, and a range of selected financial indicators such as return on capital employed, liquidity, leverage, and company size. For this reason, the analysis was based on quantitative and qualitative data derived from the annual financial reports from a sample of 56 companies listed on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 59 publications
3
14
1
4
Order By: Relevance
“…On the other hand, the findings of this study is at variance with the findings of Salaudeen and Ejeh (2018) who discovered a non-significant association between ownership concentration and tax aggressiveness in a sample of non-financial firms in Nigeria. The finding also disagrees with the finding of Chytis et al (2019) who found that the cumulative percentage of shareholders with at least 5% shareholdings had an insignificant association with tax avoidance in Greek companies.…”
Section: Discussion Of Findingscontrasting
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the findings of this study is at variance with the findings of Salaudeen and Ejeh (2018) who discovered a non-significant association between ownership concentration and tax aggressiveness in a sample of non-financial firms in Nigeria. The finding also disagrees with the finding of Chytis et al (2019) who found that the cumulative percentage of shareholders with at least 5% shareholdings had an insignificant association with tax avoidance in Greek companies.…”
Section: Discussion Of Findingscontrasting
confidence: 99%
“…One measure is the ratio of shares held by shareholders with at least 5% shares to total outstanding shares (block holdings). This is line with Chytis et al (2019). The second measure of ownership concentration (OWNCO2) is an indicator variable where 1 is assigned if the ratio of block holdings is in excess of the mean value; otherwise 0.…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…Therefore, the larger the company, the lesser the tax avoidance activities. This finding was supported by the study of Chytis, Tasios, Georgopoulos and Hortis (2019), which was carried out in Greece. Chytis et al (2019) explored the relationship between tax avoidance and corporate governance characteristics on a sample of 280 companies listed on the Athens Stock Exchange.…”
Section: Firm Sizesupporting
confidence: 62%
“…This finding was supported by the study of Chytis, Tasios, Georgopoulos and Hortis (2019), which was carried out in Greece. Chytis et al (2019) explored the relationship between tax avoidance and corporate governance characteristics on a sample of 280 companies listed on the Athens Stock Exchange. Based on the linear regression analysis conducted, the study revealed that firm size negatively influenced tax avoidance for the investigated companies.…”
Section: Firm Sizesupporting
confidence: 62%